2022
DOI: 10.1080/15627020.2022.2085063
|View full text |Cite
|
Sign up to set email alerts
|

Standardising English and Afrikaans common names for polychaetes harvested as bait in South Africa

Abstract: Supplementary material Table 5: Identification of polychaetes used as bait in the peer-reviewed literature, field guides, unpublished reports and theses, and governmentissued documents. Where possible, region where information was gather is included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In South Africa, the three most widely reported polychaete genera used as bait are Arenicola , Pseudonereis, and Gunnarea with isolated reports of onuphids used as bait ([ 22 , 23 ] Supplementary Material Tables S1–S3). One of these is of Diopatra cuprea, used in KwaZulu Natal on the east coast [ 24 ], although the collection of polychaetes has subsequently been prohibited in that province [ 23 ]. Diopatra neapolitana was reported in low densities in Swartkops [ 25 ] and Knysna in the 1950s [ 26 ], and in Keurbooms in the 1980s [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Africa, the three most widely reported polychaete genera used as bait are Arenicola , Pseudonereis, and Gunnarea with isolated reports of onuphids used as bait ([ 22 , 23 ] Supplementary Material Tables S1–S3). One of these is of Diopatra cuprea, used in KwaZulu Natal on the east coast [ 24 ], although the collection of polychaetes has subsequently been prohibited in that province [ 23 ]. Diopatra neapolitana was reported in low densities in Swartkops [ 25 ] and Knysna in the 1950s [ 26 ], and in Keurbooms in the 1980s [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was only in 2018 that Van Rensburg et al (2020) correctly identified the species as Diopatra aciculata and categorised the species as cryptogenic, as the records in South Africa [ 20 ] may predate the description in Australia [ 18 ]. Now known as the estuarine moonshine worm [ 23 ], D. aciculata is only reported in Knysna, Keurbooms, and Swartkops Estuaries [ 21 ] and is the second most popular polychaete bait species in the Knysna Estuary after Arenicola loveni [ 31 ]. Since the 2000s, the population of D. aciculata in Knysna has increased in size with recent population estimates indicating approximately 20 to 24 million individuals [ 21 ].…”
Section: Introductionmentioning
confidence: 99%